2019
DOI: 10.1186/s12955-019-1191-0
|View full text |Cite
|
Sign up to set email alerts
|

The association between elderly people’s sedentary behaviors and their health-related quality of life: focusing on comparing the young-old and the old-old

Abstract: Background Research on the effects of sedentary behavior on the health-related quality of life (HRQoL) of the elderly is limited. The present study aimed to determine the association between sedentary behavior and the HRQoL of the young-old (aged 65–74 years) people and old-old (aged ≥75 years) people. Methods This study used the raw data of the 7th Korea National Health and Nutrition Examination Survey for 2016. The study subjects were 1,415 people aged over 65 years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 29 publications
3
55
0
6
Order By: Relevance
“…According to the literature, sedentary behaviors (activities with an energy cost of less than 1.5METs such as sitting and lying down) are associated with an increased risk of various diseases including type II diabetes, CVD and mortality in the long run [22]. In addition, the condition for sedentary behaviors increases with increasing age and retirement.It has also been reported that older people spend about 60 percent of their awake time in the sitting position [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the literature, sedentary behaviors (activities with an energy cost of less than 1.5METs such as sitting and lying down) are associated with an increased risk of various diseases including type II diabetes, CVD and mortality in the long run [22]. In addition, the condition for sedentary behaviors increases with increasing age and retirement.It has also been reported that older people spend about 60 percent of their awake time in the sitting position [22].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that the incidence and mortality rate of CVD, diabetes, cancer and stroke is up to two times higher in inactive elderly than in those with high levels of PA [20]. In addition, the results of recent research show that leisure-time exercise was associated with the prevention and control of cardiovascular, metabolic, hypertensive, osteoarthritis, and reduced drug consumption, as well as a 28% reduction in mortality risk in the elderly [12,21,22].…”
Section: Introduction mentioning
confidence: 99%
“…In a previous study, we observed that aquatic training improved muscle strength and flexibility in sedentary lifestyle elderly women [1,2]. However, some participants also mentioned balance improvement a er aquatic training.…”
Section: Introductionmentioning
confidence: 87%
“…Sedentary behavior is inversely associated with quality of life in older adults. Besides, it has been associated to a higher risk of developing obesity, type-2 diabetes, bone hypodensity, and cardiovascular diseases [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation